Behavioral Implications of Taxation. - Crumbley, D. Larry (The Accounting Review, 1973)
Abstract The article argues that behavioral implications should be considered in the formulation of tax law and policy in the United States. The income tax policy of the United States has many objectives including raising revenue, encouraging economic growth, stabilizing the economy, redistributing income and wealth and encouraging certain industries. Although taxation does influence human behavior, most tax laws are enacted without adequate consideration of their behavioral effects. A person on welfare cannot better himself by working unless he can get off welfare altogether. Proponents of the negative income tax, both conservatives and liberals, indicate that under a negative income tax system the individual's payments would not be reduced dollar-for-dollar as earnings rise. The households were drawn from a stratified sample of eligible households and were assigned to either an experimental or control group. An increase in income has had little impact on family stability. The power of incentives and disincentives is enormous. They may be used to safeguard or to exploit, to subsidize one interest or to destroy another, to simplify administration or to confuse it. Taxation does influence human behavior, but the important thing is to learn which provisions influence behavior in what way– and whether the resulting behavior is that which is desired.